2010
DOI: 10.3390/cancers2020752
|View full text |Cite
|
Sign up to set email alerts
|

Viruses and Breast Cancer

Abstract: Viruses are the accepted cause of many important cancers including cancers of the cervix and anogenital area, the liver, some lymphomas, head and neck cancers and indirectly human immunodeficiency virus associated cancers. For over 50 years, there have been serious attempts to identify viruses which may have a role in breast cancer. Despite these efforts, the establishment of conclusive evidence for such a role has been elusive. However, the development of extremely sophisticated new experimental techniques ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 79 publications
5
50
0
Order By: Relevance
“…The detection of HPV in breast cancer is consistent with 15 (of 17) previous publications reporting the presence of HPV in breast cancer world-wide with a prevalence of ranging from 4 -86% (Lawson et al, 2006). Given such a high proportion of studies reporting HPV in breast cancer and breast tissue, the question is why some (2 of 17) studies report that HPV is not present in breast cancer.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The detection of HPV in breast cancer is consistent with 15 (of 17) previous publications reporting the presence of HPV in breast cancer world-wide with a prevalence of ranging from 4 -86% (Lawson et al, 2006). Given such a high proportion of studies reporting HPV in breast cancer and breast tissue, the question is why some (2 of 17) studies report that HPV is not present in breast cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have demonstrated the presence of HPV high-risk types 16, 18 and 33 in breast cancer specimens from diverse populations around the world: Italy, Norway, China, Japan, USA, Austria, Brazil, Australia, Taiwan, Turkey, Greece, Korea, Mexico, Hungary and Syria (Lonardo et al, 1992;Hennig et al, 1999;Yu et al, 1999;Liu et al, 2001;Damin et al, 2004;Widschwendter et al, 2004;de Villiers et al, 2005;Kan et al, 2005;Tsai et al, 2005;Gumus et al, 2006;Kroupis et al, 2006;Lawson et al, 2006;Choi et al, 2007;Akil et al, 2008;Khan et al, 2008;Kulka et al, 2008;MendizabalRuiz et al, 2009). The prevalence of HPV positive breast cancer in these studies was reported to vary from 4% in Mexican to 86% in American women.…”
mentioning
confidence: 99%
“…Such evidence may provide opportunities for the pathogenesis, early detection and prevention of breast cancer (5,58,59). In particular, along with the reports of worse prognosis of EBV DNA positive patients than the negative patients (12,34,37), this can be applied to the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although we used the TaqMan realtime PCR and MMTV isolate as a positive control, we did not detect MMTV in our CMT tissue samples. This difference may be due to the previously described relationship between MMTV and BC and the presence of house mouse in the domestic or work environment (13,23). Stewart et al (21) predicted that "people who live and work where Mus domesticus is especially common should have a higher MMTV sero-prevalence than those not so directly exposed to mice".…”
Section: Methodsmentioning
confidence: 99%
“…Due to these effects, Lawson and Heng (13) believed that the scientific issue has evolved from "are viruses present in BC?" to "are viruses in BC oncogenic or harmless passengers?"…”
Section: Introductionmentioning
confidence: 99%